Drug utilisation pattern in geriatric patients of a teritiary care teaching hospital: a retrospective study - Tamma, Naveen Kumar; Patnaik, Prasanth Kumar; Karedla, Srinivasu (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The objective of the study was to assess the prescribing pattern of drugs in geriatrics patient in a tertiary care hospital. Methods: A retrospective observational study was conducted by department of Pharmacology for a period of one year in patients above 65 years from case sheets of medical record section. WHO basic indicators were used for studying the prescribing pattern of drugs. Results: A total of 200 patients were included in the study. Respiratory tract and gastrointestinal infections were most commonly found among patients of geriatric age group. Among antibiotics ceftriaxone, cefixime, ampicillin, amoxicillin, azithromycin, ciprofloxacin, cotrimaxazole for upper respiratory tract infections and rantidine, norfloxacin for gastrointestinal tract infections were maximum utilized. Polypharmacy was prevalent and majority of drugs prescribed were by brand names because of free supply of drugs. Conclusions: There is a need to bring changes in the prescribing practices with particular emphasis on generic drug and restricting polypharmacy. Also antibiotic policy needs to be introduced in the hospital and continuous medical education besides evidence based medicine approach for rationale use of drugs.